2018
DOI: 10.11606/s1518-8787.2018052000933
|View full text |Cite
|
Sign up to set email alerts
|

Area deprivation measures used in Brazil

Abstract: OBJECTIVETo describe and assess currently used area-based measures of deprivation in Brazil for health research, to the purpose of informing the development of a future small area deprivation index.METHODSWe searched five electronic databases and seven websites of Brazilian research institutions and governmental agencies. Inclusion criteria were: studies proposing measures of deprivation for small areas (i.e., finer geography than country-level) in Brazil, published in English, Portuguese or Spanish. After dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Socioeconomic status is considered one of the most consistent health determinants of a population, hence the importance of identifying the population segments that still live in poverty. This identification also enables the monitoring of health inequalities, the understanding of their causes and favors the evaluation of the impact of social programs on reducing inequalities (39) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status is considered one of the most consistent health determinants of a population, hence the importance of identifying the population segments that still live in poverty. This identification also enables the monitoring of health inequalities, the understanding of their causes and favors the evaluation of the impact of social programs on reducing inequalities (39) .…”
Section: Discussionmentioning
confidence: 99%
“…Social deprivation should be taken into account in order to decrease infant mortality inequalities (39,42) . Yun et al (41) suggested establishing a regional perinatal assistance and medical emergency system in underprivileged regions, along with surveillance and monitoring of pregnant women and newborns in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil is still considered poor, with substantial internal disparities, even with the improvement of the Human Development Index. 28,29 The 80 couples evaluated here were classified as belonging to social class C, with monthly income between 4 and 10 minimum wages (R$3748.01-R$9370.00 [$961.00-$2402.00]), and demonstrated a WTP value of R$18 720.18 using the direct question and R$22 831.17 for the payment scale techniques. It then becomes clear how couples attribute a strong psycho-emotional component to the decision to undergo IVF treatment and are most likely to give up other leisure, comfort, and heritage achievements in the realization of this marital life project to have a child.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed scoping review will be conducted in accordance with the JBI methodology for scoping reviews [18]. We have not registered this review with PROSPERO, because a scoping review is not registered with PROSPERO.…”
Section: Methodsmentioning
confidence: 99%
“…• To create a list and taxonomy of deprivation indices A preliminary search of PubMed found a recently published scoping review from 2018 by Ichihara et al on area deprivation measures used in Brazil. [18] Ichihara et al included 30 articles. The main goals of this scoping review were to inform the development of a small-area deprivation index for Brazil and review the literature to describe currently used area-based measures of socioeconomic inequalities in Brazil.…”
Section: Introductionmentioning
confidence: 99%